A função social dos direitos autorais como concretização do direito fundamental à educação - Cardoso, Paulo Arthur de Oliveira (2017)
Before the new informational technologies, which allow a wider exchange of cultural goods in despite of law, this paper aims to answer the following question: how to combine the autor’s fundamental right to property with population’s fundamental right of access to education? For doing so, it is pursued in the social function of copyright the point of balance between the two mentioned fundamental rights. In this goal, it is adopted the deductive and hipotetic-deductive methods, aiming to demonstrate the social function of copyright as one of the premisses to the concretization of the rights to acess to culture and education. It is also analyzed the copyright law and the problems posed for it in the informational society. It is studied the right to education in its formal and informal dimensions, just as its relation with cultural goods. From this point, it is investigated the correlation of cultural goods with education and ciberspace. It is also pondered the social function of property in the midst of copyright, in its patrimonial dimension. It is concluded, in the end, about the need of an alteration of copyright law and also it is intended to present some hipotesis for the resolution of the posed problem and its feasabilities.